NIGERIA’S BILATERAL TRADE RELATIONS WITH CHINA: AN ASSESSMENT, 2010 – 2019 - Halidu, Agaba; Atnadu , David Fidelis (International Journal of Multidisciplinary Research and Studies, 2022)
This work is an assessment of Nigeria-Sino bilateral trade relations. This assessment was done using secondary sources of data such as books, journals, newspapers, etc. Dependency theory was used to examine the trade relations between Nigeria and China to show how dependent Nigeria is on China. Nigeria needs China for finished goods and getting loans and China need Nigeria for certain raw materials but Nigeria has over time been dependent on China and this has increased the Nigerian debt burden. The study discovered that trade imbalance in the bilateral relations persisted and, that the bilateral trade relations have made Nigeria dependent on China. The study also discovered that trade relations benefited the two countries within this period and China benefited more due to the persistent trade imbalance. After seeing all these, the study made the following recommendations: Nigeria needs to invest massively in the manufacturing sector in order to close the massive gap in the economic strength between the two countries, and the two countries should do more to increase foreign direct investment (FDI), Nigeria should do more in exporting finished goods to China and this can be actualized through massive industrialization.